Greenhouse gas balance and mitigation of pasture-based dairy production systems in the Brazilian Atlantic Forest Biome - Oliveira, Patrícia Perondi Anchão; Berndt, Alexandre; Pedroso, André de Faria; Alves, Teresa Cristina; Lemes, Amanda Prudêncio; Oliveira, Bia Anchão; Pezzopane, José Ricardo Macedo; Rodrigues, Paulo Henrique Mazza (Frontiers in Veterinary Science, 2022)
Brazilian cattle production is mostly carried out in pastures and the need to reduce the sector's greenhouse gas (GHG) emissions and its environmental footprint has become a priority. The adoption of well-suited breeds and intensification of pasture-based livestock production systems are an alternative to optimize the sector's land usage. The objective of this research was to evaluate the effect of Holstein and Jersey-Holstein crossbred cows in different levels of pastures intensification (continuous grazing system with low stocking rate–CLS; irrigated rotational grazing system with high stocking rate–RHS) on the GHG mitigation. Twenty-four Holstein and 24 Jersey-Holstein crossbred dairy cows were used to evaluate the effect of two grazing systems on milk production and composition, soil GHG emissions, methane emission, soil carbon accumulation (0-100 cm). These variables were used to calculate the C-balance, GHG emission intensity, number of trees required to mitigate GHG emission and land-saving effect. The C-balance of all systems and genotypes presented a deficit in carbon; there was no difference for genotypes, but RHS was more deficient than CLS (-4.99 to CLS and -28.72 to RHS ton CO2e..ha-1.year-1). The deficit of C on GHG emission intensity was similar between genotypes and higher for RHS (-0.480 to RHS and -0.299 to CLS kg CO2e..kg FCPCmilk-1). Lower GHG removals (0.14 to CLS higher than 0.02 to RHS kg CO2e..kg FCPCmilk-1) had the greatest influence on the GHG emission intensity of milk production. The trees required to mitigate GHG emission was calculated, considering the C balance within the farm gate. The deficit number of trees to abatement emissions was higher to HO (-46.06 to HO and -38.37 trees/cow to JE x HO) and to RHS (-51.9 to RHS and -33.05 trees/cow to CLS). However, when the results are expressed per ton of FCmilk, there was a difference only for pasture management, requiring - 6.34 tree/ton FCmilk for the RHS and -3.99 tree/ton FCmilk for the CLS system. The pastures intensification resulted in higher milk production and land-saving effect of 2.7 ha for each ha of intensified pasture.